Studies on noradrenergic and serotonergic modulation of dopamine neurotransmission in the rat brain [Microfiche] - Nurse, Barbara (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1987.